"Spirit in a World without Spirit" - Foucault’s Interpretation of the Iranian Revolution and Resistance to Western Modernity - Urosevic, Milan (Serbian political thought, 2024)
In this article, we analyze Foucault’s research of the Iranian Revolution, conducted at the end of 1978. This research has made Foucault the target of numerous criticisms from his contemporaries, while later interpreters of his work have tried in various ways to understand how this research relates to the rest of his oeuvre. A review of the relevant literature shows that there are different currents in interpreting the place that the study of the Iranian Revolution has in Foucault’s work. One of these currents argues that Foucault was “seduced” by the “irrational” aspects of Islam because his theoretical and epistemological standpoints inherently contain anti-Enlightenment aspects. A certain number of authors also agree on the interpretation that sees inconsistency in Foucault’s study of the Iranian Revolution, as they believe that at this point, he abandons his understanding of power as a totalizing mechanism and introduces the idea of a free acting subject. We will attempt to show that both currents miss the most important aspect of Foucault’s research of the Iranian Revolution, which is the way this research fits into his academic interests at that time. Specifically, we will try to locate his study of the Iranian Revolution within the framework of his academic research in the late 1970s, as well as show how the socio-political context of France at that time influenced his work. We will start the article by examining the relationship between French left-leaning intellectuals and the French Communist Party during this period, as well as their stance on the coalition between the French Communist Party and the Socialist Party. We will show that due to the influence of cooperation with Maoist organizations and his participation in the student revolt of 1968, Foucault developed a negative attitude towards the Stalinist orientations of the French Communist Party and therefore at that time tries to develop a theoretical framework for a non-Marxist understanding of macro-social reality. In such a context, Foucault develops his theory of “governmentality”, which refers to the specific logic of social relations that regulates the institutions of society in a given historical period. The set of institutions and social relations that governmentality regulates he calls a “dispositive”. Foucault’s research leads him to the conclusion that the dispositive regulating contemporary society is guided by the logic he calls “pastoral governmentality”, claiming that it involves regulating individuals’ actions through their dimension of subjectivity, i.e., through the way they relate to themselves and manage their behavior. Furthermore, he demonstrates how this logic, rooted in the Catholic Church, extends to other social institutions from the seventeenth century and becomes associated with the capitalist mode of production in the eighteenth century. It then assumes a role in regulating individuals’ subjectivity in accordance with the concept of the individual as homo economicus. Aligning with his concept of governmentality, Foucault develops the notion of “counter-conduct” as a form of resistance to pastoral governmentality. This idea involves rejecting the prescribed model of subjectivity and, consequently, developing practices that transcend the power relations shaped by pastoral governmentality. We will demonstrate that Foucault’s research of the Iranian Revolution serves as a real-time, practical test of his idea of counter-conduct. Namely, he claimed that the reforms of the Iranian Shah aimed at establishing a dispositive guided by the pastoral logic of governmentality. Therefore, he sees the Iranian Revolution as a collective revolt against the dispositive that has been dominant in Western countries since the seventeenth century. In his study of the Iranian Revolution, he is particularly interested in the role of Shia Islam in regulating practices of resistance. He sees Shiism as the discourse through which the Iranian Revolution as a collective form of counter-conduct is coordinated and argues that this form of Islam allows revolutionaries to transform their subjectivity by rejecting the model of subjectivity prescribed by pastoral governmentality. Finally, the article concludes with a review of two ways in which the study of the Iranian Revolution fundamentally affects Foucault’s work. The first way involves a shift in the focus of his research, which from 1979. becomes centered on the phenomenon of subjectivity. Thus, during the 1980s, Foucault’s work involves exploring various models of subjectivity in the history of Western culture. The second influence of the Iranian Revolution can be observed in Foucault’s renewed focus on the concept and phenomenon of the Enlightenment.